Autis, dukungan keluarga, HUBUNGAN DUKUNGAN SOSIAL KELUARGA DENGAN PENERIMAAN DIRI IBU ANAK AUTIS DI SDLB-B DAN AUTIS - Lantin Sulistyorini (Jurnal Keperawatan Malang, 2018)
Self acceptance is an attitude that reflects the feelings of a person based on the fact that existed in them. People who accept themselves well will be able to accept their own weakness and excess. One of the factors that influence the mother self acceptance of children with autism is family social support. The purpose of this study was to determine the correlation between family social support and mother self acceptance of children with autism in SDLB–B and Autism TPA in Patrang District Jember Regency. This study used observational analytic design with cross sectional approach. The sample was 19 mothers of children with autism that selected using the total sampling. Data were analyzed by Chi-Square test. The results showed that p-value 0,024 < α 0,05 so it can be concluded there is a relationship between family social support with self acceptance mother of children with autism in SDLB–B and Autism TPA in Patrang District Jember Regency. OR value of 13,5 means mothers with good family social support have the opportunity 13,5 times to having a good self acceptance than mothers with less family social support. Based on the research results, it is suggested for the family to improve the social support to mothers with autistic children. Keywords: autism, family social support, self acceptance